Embedding Ultrasmall Au Clusters into the Pores of a Covalent Organic Framework for Enhanced Photostability and Photocatalytic Performance. Issue 15 (20th February 2020) - Deng, Yang; Zhang, Zhen; Du, Peiyao; Ning, Xingming; Wang, Yue; Zhang, Dongxu; Liu, Jia; Zhang, Shouting; Lu, Xiaoquan
Abstract: Gold clusters loaded on various supports have been widely used in the fields of energy and biology. However, the poor photostability of Au clusters on support interfaces under prolonged illumination usually results in loss of catalytic performance. Covalent organic frameworks (COFs) with periodic and ultrasmall pore structures are ideal supports for dispersing and stabilizing Au clusters, although it is difficult to encapsulate Au clusters in the ultrasmall pores. In this study, a two‐dimensional (2D) COF modified with thiol chains in its pores was prepared. With −SH groups as nucleation sites, Au nanoclusters (NCs) could grow in situ within the COF. The ultrasmall pores of the COF and the strong S−Au binding energy combine to improve the dispersibility of Au NCs under prolonged light illumination. Interestingly, Au–S–COF bridging as observed in this artificial Z‐scheme photocatalytic system is deemed to be an ideal means to increase charge‐separation efficiency. Abstract : Building bridges : A covalent organic framework (COF) was modified with thiol chains as nucleation sites for gold nanoclusters (NCs) in its pores. The Au–S–COF bridges in the resulting photocatalyst increased charge‐separation efficiency (see picture). Furthermore, the ultrasmall pores of the COF and the strong S–Au binding energy combined to improve the dispersibility of Au NCs and their photostability under prolonged illumination.